The Testing of a Four-Dimensional Model of Athlete Leadership and Its Relation to Leadership Effectiveness - Maechel, Christopher; Loughead, Todd M.; Beckmann, Jürgen (Frontiers in Psychology, 2020)
Athlete leadership researchers have typically investigated three dimensions of athlete leadership behaviors, which include the meta-categories of task-, social-, and external-oriented leadership. More recently, motivational leadership was added as a fourth dimension. Researchers in organizational leadership have advanced another dimension referred to as change-oriented leadership (Yukl, 2012). Therefore, in the present study, we tested a four-dimensional model that includes the dimensions of task-, social-, external- and change-oriented leadership. Two samples of 161 athletes and 69 coaches rated every player on their team on the four-dimensional model and on perceived athlete leadership effectiveness. A multilevel regression analysis showed that all four dimensions of athlete leadership significantly predicted perceived athlete leadership effectiveness for players and three dimensions (i.e., social, task, and change-oriented leadership) for coaches. These results support the importance of change-oriented leadership in relation to athlete leadership.